2017
DOI: 10.4103/ijo.ijo_560_16
|View full text |Cite
|
Sign up to set email alerts
|

A 7-year-old female child of incontinentia pigmenti presenting with vitreous hemorrhage

Abstract: Incontinentia pigmenti (IP) is a rare disease with multisystemic anomalies, which commonly presents just after birth. Here, we report a rare case of IP patient with vitreous hemorrhage in school-age children. Therefore, physicians have to be alert and evaluate IP patients at all ages. Regular ophthalmic follow-up is necessary, and fluorescein angiography should be performed if peripheral ischemia or neovascularization is suspected. The effect of peripheral laser ablation on peripheral retinal nonperfusion is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…These ophthalmologic lesions are mainly retinal vascular abnormalities, including peripheral retinal avascular areas, abnormal vascular anastomosis, and peripheral peripherals. 11 Vascular loop-like changes have also been reported that in addition to changes in peripheral blood vessels, patients often have decreased blood flow density in the macular area. 12 Other eye diseases include strabismus, cataracts, optic nerve atrophy, retinal pigment epithelial abnormalities, retinal detachment, and microphthalmia.…”
Section: Discussionmentioning
confidence: 98%
“…These ophthalmologic lesions are mainly retinal vascular abnormalities, including peripheral retinal avascular areas, abnormal vascular anastomosis, and peripheral peripherals. 11 Vascular loop-like changes have also been reported that in addition to changes in peripheral blood vessels, patients often have decreased blood flow density in the macular area. 12 Other eye diseases include strabismus, cataracts, optic nerve atrophy, retinal pigment epithelial abnormalities, retinal detachment, and microphthalmia.…”
Section: Discussionmentioning
confidence: 98%
“…A wide array of ophthalmic manifestations associated with IP have been reported and this includes nystagmus, strabismus, microphthalmos, cataract, glaucoma, optic atrophy, foveal hypoplasia, retinal avascularity, retinal neovascularisation, vitreous haemorrhage and tractional retinal detachment 8–10. Ophthalmic manifestations of IP in infants are vision threatening and their clinical presentation can at times mimic retinopathy of prematurity (ROP), familial exudative vitreoretinopathy (FEVR) and Norrie’s disease 11.…”
Section: Discussionmentioning
confidence: 99%